Clinical Characteristics and Factors Associated with Disease Progression in Chinese Patients with Connective Tissue Disease and Pulmonary Arterial Hypertension - Zhang, Haichao; Liu xiaoyan, Xiaoyan (Aktuelle Rheumatologie, 2020)
Objective To clarify the characteristics, survival, and predictors of mortality in Chinese patients with pulmonary arterial hypertension (PAH) associated with connective tissue disease (CTD).Methods This single-cohort study involved 67 CTD-PAH patients who visited Shanghai Renji Hospital between January 2011 and January 2019. Baseline clinical features and hemodynamic parameters were recorded. Logistic regression was used to determine the independent factors associated with mPAP improvement.Results SLE was the major underlying CTD, affecting 70% of PAH patients, whereas systemic sclerosis was less common (6%). Modern PAH drug use was associated with a favorable outcome and mPAP improvement.Conclusion The majority of the CTD-PAH population in China suffers from SLE in contrast to the CTD-PAH patients in the USA and Europe. Pulmonary vasodilation treatment has improved the mPAP in these patients.
Keywords: pulmonary arterial hypertension; systemic lupus erythematosus; connective tissue disease